Greenhouse gases emitted by agricultural vehicles in Costa Rica (UNED Research Journal, 2021)
Introduction: In Costa Rica, greenhouse gas emissions from agricultural vehicles are not usually measured independently in inventories. They are usually pooled within overall vehicle fleet or other emissions. Objective: Determine the emissions and specific characteristics for agricultural vehicles in Costa Rica. Methods: The basic characteristics of agricultural machinery in Costa Rica were obtained from information on the payment of circulation taxes for the year 2016. The estimate of emissions was based on the parameters established by the Intergovernmental Panel on Climate Change and factors specific to Costa Rica. Results: Most agricultural machinery is less than 10 years old (92%), uses diesel fuel (99%) and is concentrated in the medium power range (category II ASAE S482, 82%). The total emissions of the equipment under study are 467 650 tons of CO2 equivalent, mainly associated with CO2 emissions (98%). This is equivalent to 10% of emissions in the Transport sector and up to 6% in the Greenhouse Gas Inventory (GHGI). Conclusions: In Costa Rica, emissions from agricultural vehicles are not properly segregated and possibly not properly accounted for. This should be improved in the country's 2050 decarbonization plan.
Keywords: Agricultural machinery; Emissions; IPCC Factors; Descarbonization; Power Engine